2014
DOI: 10.1002/pros.22853
|View full text |Cite
|
Sign up to set email alerts
|

Different gDNA content in the subpopulations of prostate cancer extracellular vesicles: Apoptotic bodies, microvesicles, and exosomes

Abstract: BackgroundExtracellular vesicles (EVs) are cell-derived membrane vesicles. EVs contain several RNAs such as mRNA, microRNAs, and ncRNAs, but less is known of their genomic DNA (gDNA) content. It is also unknown whether the DNA cargo is randomly sorted or if it is systematically packed into specific EV subpopulations. The aim of this study was to analyze whether different prostate cancer (PCa) cell-derived EV subpopulations (apoptotic bodies, microvesicles, and exosomes) carry different gDNA fragments.MethodsEV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
184
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 247 publications
(190 citation statements)
references
References 27 publications
6
184
0
Order By: Relevance
“…Perhaps the difference lies in the fact that chromosomal DNA becomes fragmented primarily during apoptosis, and such fragmentation does not occur in our studies. Interestingly, EVs from cancer patients have recently been shown to contain genomic DNA fragments (25)(26)(27) that may be derived from the fragmented chromosomes of tumor cells undergoing apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps the difference lies in the fact that chromosomal DNA becomes fragmented primarily during apoptosis, and such fragmentation does not occur in our studies. Interestingly, EVs from cancer patients have recently been shown to contain genomic DNA fragments (25)(26)(27) that may be derived from the fragmented chromosomes of tumor cells undergoing apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…The presence in the TEX cargo of DNA, mRNA, and miRs is important for the role of TEX as information-carrying vehicles. TEX derived from tumor cell lines and EVs from the plasma of cancer patients contain double-stranded genomic DNA (gDNA) (81). Analyses of gDNA fragments of MLH1, PTEN, or TP53 genes showed that different exosomes had distinct gDNA content that could include specific mutations (81,82).…”
Section: Functional Attributes Of Texmentioning
confidence: 99%
“…TEX derived from tumor cell lines and EVs from the plasma of cancer patients contain double-stranded genomic DNA (gDNA) (81). Analyses of gDNA fragments of MLH1, PTEN, or TP53 genes showed that different exosomes had distinct gDNA content that could include specific mutations (81,82). TEX have the ability to carry and transfer oncogenic mutations to recipient cells (83).…”
Section: Functional Attributes Of Texmentioning
confidence: 99%
“…Some studies have also reported the presence of double stranded genomic DNA (gDNA) in diverse types of EVs [11]. Results from one of the first studies on DNA in EVs demonstrated that different EV populations (apoptotic bodies, microvesicles and exosomes) harbour either TP53 or PTEN mutations [12], suggesting specific EV types might package different parts of the genome. EVs can also carry mitochondrial DNA, retrotransposons and oncogenes (i.e.…”
Section: Introductionmentioning
confidence: 99%